1983
DOI: 10.1051/jphys:0198300440110130700
|View full text |Cite
|
Sign up to set email alerts
|

Infrared transmission of heavily doped polyacetylene

Abstract: 2014 Dans ce travail nous présentons des résultats de mesures de transmission et réflexion dans le domaine infrarouge (4 03BCm-25 03BCm) effectuées sur des films de polyacétylène. Les mesures ont été faites sur des échantillons de polyacétylène [CH(I3-)Y]x de diverses épaisseurs pour des taux Y de dopage à l'iode allant de 0 à 7 %. La méthode utilisée permet d'obtenir des spectres sur des films libres de tout support. De plus contrairement aux techniques usuelles elle permet de travailler, à fort dopage sur de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1985
1985
1993
1993

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…The 900 cm-' one warps and shifts also towards high frequencies. This result is quite different from that observed with usual (CH), in which upon increasing the dopant level the shift is towards low frequencies [39,47]. The authors think that the observed behaviour could arise from the differences in conjugated length.…”
Section: Modified Polyacetylene and Related Polymerscontrasting
confidence: 80%
See 3 more Smart Citations
“…The 900 cm-' one warps and shifts also towards high frequencies. This result is quite different from that observed with usual (CH), in which upon increasing the dopant level the shift is towards low frequencies [39,47]. The authors think that the observed behaviour could arise from the differences in conjugated length.…”
Section: Modified Polyacetylene and Related Polymerscontrasting
confidence: 80%
“…Thus the origin of the enhanced IRAV mode intensities in heavily doped polyacetylene remains an important, unresolved, problem (Kim and Heeger [52]). Following the conclusion of [47] we deduce that the 900 cm-' mode could have a molecular origin which should be determined. At this point we must indicate that an alternative explanation can be proposed.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The logarithm of transmittance is given by where R is the reflection factor and x the sample thickness. Reflectivity measurements on non-oriented doped sample [9] show that R increases with doping level from 0.1 to 0.3 when conductivity varies from 1 0 P to lof1 Q-l cm-l. Thus, there is evidence that the observed very high value of polarization degree is not due to reflection but rather arises from absorption.…”
Section: Analysis Of Resultsmentioning
confidence: 94%